Evolutionary shifts in gene expression decoupled from gene duplication across functionally distinct spider silk glands - Thomas H. Clarke (Nature Portfolio, 2017)
Abstract Spider silk synthesis is an emerging model for the evolution of tissue-specific gene expression and the role of gene duplication in functional novelty, but its potential has not been fully realized. Accordingly, we quantified transcript (mRNA) abundance in seven silk gland types and three non-silk gland tissues for three cobweb-weaving spider species. Evolutionary analyses based on expression levels of thousands of homologous transcripts and phylogenetic reconstruction of 605 gene families demonstrated conservation of expression for each gland type among species. Despite serial homology of all silk glands, the expression profiles of the glue-forming aggregate glands were divergent from fiber-forming glands. Also surprising was our finding that shifts in gene expression among silk gland types were not necessarily coupled with gene duplication, even though silk-specific genes belong to multi-paralog gene families. Our results challenge widely accepted models of tissue specialization and significantly advance efforts to replicate silk-based high-performance biomaterials.